Treinadores(as) em formação universitária: percepções sobre conhecimentos e competências - Santos, Yura Yuka Sato dos (2022)
The aim of this case study was to analyze the perceptions of students from a Sports Science program in Brazil regarding the attributed importance and domain perceived over the knowledge and competences of the sports coach. We used the questionnaire by Quinaud et al. (2018), with 192 students from the first to the fifth year of the program. We used descriptive statistics and, after verifying the non-normal distribution, we used the Kruskal-Wallis test to compare the assigned importance and the perceived domain within the groups. In cases with significant differences, we used the Mann-Whitney U test, Dun-Bonferroni correction (p≤0.05) and effect size by partial Eta² (Cohen, 1973). We did not find significant differences regarding the importance attributed to knowledge and we observed differences in two competences. Regarding the perceived domain, we found significant differences regarding all knowledge and competences, especially among students from the first years compared to those of the 3rd, 4th and 5th. Different experiences throughout the course seem to help in the development of the students' knowledge and competences. Considering that in Brazil there is a requirement for an undergraduate degree to work as a coach, it is important that Physical Education and Sport programs focus on the development of specific knowledge and competences of this profession.